Direito e financiamento na educação infantil de 0 de 3 anos - um estudo exploratório dos processos de privatização no município de São Paulo - Silva, Gicelia Santos (2020)
The changes in the conception of childhood appear with more emphasis in the Modern world and have been intensified throughout the 20th century. In Brazil, they promoted the introduction of public policy in which the educational right is recognized. This has changed the assistance of 0 to 3 years old children from the Social Assistance to the Education area consolidated it in the Federal Constitution 1988 and in the National Education Guidelines Diretrizes e Bases da Educação Nacional - 1996, delegating to the city scope the provision of school assistance to children. This dissertation investigates the early childhood education system in the City of São Paulo from 2005 to 2018. In addition, its research aims at analyzing the political-legal foundations of the partnership policy of São Paulo municipal government. It seeks to answer the following research question: What are the public policy concepts that underlie the partnership strategy of the São Paulo municipal executive branch of government, understood as privatization process? This question derives from the general objective of understanding the political and legal foundations of the private partnership policy, the attainment of which will be preceded by the following specific goals: a) identify the political arguments that guided the funding and legal formulation strategies of municipal policies for early childhood education; b) by means of a survey of statistical data on childcare in the municipal public network of São Paulo, identify the evolution of the values destined to the partner network and the evolution of the number of enrollments and schools in the direct, indirect and private networks. This is a quantitative and qualitative research of a theoretical nature and of a documentary and bibliographic type. Data collection was carried out through research: i. primary sources, with a focus on educational legislation, the city budget and enrollment and school data, comprising the three distinct networks; ii. academic bibliographic sources on childhood, the right to early childhood education, funding and privatization. The theoretical framework is based on authors who have developed studies in the field of the right to education, funding, and privatization, including Mascaro, Adrião, Pinto, Arelaro, Freitas, Peroni, and Silva. The analytical path followed the historical trajectory of the concept of childhood, children and their educational assistance, the legal positivization of rights for children, the funding policy for this educational stage and the proposed care and management strategies, especially those that are guided towards the privatization of this teaching stage. The categories - Right to Education, Funding and Privatization - will be used to describe the historical-political context that has triggered public policies for this sector of education in the period in question. The method of approach will be Historical-Dialectic Materialism, which considers the contradictions that present themselves in socio-political life and, thus, allows us to understand the research object in its entirety, in dialogue with historical, social and economic aspects. The analysis of the data allowed to identify the deepening of the privatization policy in the offer of places for Early Childhood Education in the City of São Paulo, by making this service more flexible.